(untitled) (Journal of Namibian Studies : History Politics Culture, 2025)
This article examines the Algerian Revolution and its image and manifestations in African liberation literature and addresses Algerian backing of African liberation movements and struggles, especially in South Africa and Portuguese colonies, including Angola and Mozambique, and explores how the revolution inspires key figures, such as South African Nelson Mandela, Ghanaian leader Kwame Nkrumah, Guinean activist Amílcar Cabral, and French-Algerian revolutionary Frantz Fanon. The writing of these activities is imbued with pride and respect for the Algerian struggle. These writings are the finest evidence of African solidarity with the Algerian Revolution, and the struggle literature of the time embodied a means of denouncing colonialism and supporting just causes in Africa.